PERANCANGAN ALAT BANTU DENGAN METODE CONJOINT ANALYSIS DAN QUALITY FUNCTION DEPLOYMENT (QFD) BERDASARKAN PRINSIP ERGONOMI - Glisina Dwinoor Rembulan; Septiawan Maratama (JIEMS (Journal of Industrial Engineering and Management Systems), 2022)
The industrial sector in Indonesia has experienced rapid development in the last 10 years. The manufacturing industry is the sector that contributes the largest export value at USD 105.11 billion or Rp. 1,438 trillion (exchange rate of Rp. 13,686/USD) during January to October 2019. PT. PJM is a manufacturing company that produces electrical panels. In production activities, PT. PJM still does a lot of work manually or Manual Material Handling (MMH) and has poor work postures. MMH activities and wrong and inappropriate work postures are the main sources of worker complaints that can pose ergonomic risks to workers. Ergonomics intervention in the design of assistive devices is carried out to help prevent the risk of MSDs and ergonomics in the workplace. The purpose of this study was to improve work posture and reduce the risk of MSDs in workers. The results of this study indicate that the highest exposure level is at the welding station, namely 60.79%, which is included in the category that needs further research and changes are made. However, after implementing the design of assistive devices at the welding station, there was a decrease in the exposure level value of 33.59%, which was included in the safe category. The implementation of the design of the tool has succeeded in improving the work posture and the risk of MSDs of workers at the welding station.